Polystyrene nanoplastics alleviate the toxicity of CuO nanoparticles to the marine algae Platymonas helgolandica var. tsingtaoensis - Liu, Fei-fei; Gao, Zhi-yin; Chu, Wang-chao; Wang, Su-chun (Frontiers in Marine Science, 2022)
The increasing presence of pollutants such as engineered nanoparticles (ENPs) and nanoplastics (NPLs) poses potential risks to the marine environment. However, there is a scarcity of information on their joint toxic effects. In this study, we investigated the toxicity of copper oxide nanoparticles (nCuO) combined with polystyrene nanoplastics (PS-NPLs) on the marine microalgae Platymonas helgolandica var. tsingtaoensis. The inhibitory effect of nCuO increased with increasing concentrations, and nCuO ≥ 100 mg/L significantly restrained the growth and chlorophyll content of microalgae. nCuO could be adsorbed by algal cells, which was responsible for membrane lipid oxidation and the disruption of membrane permeability. Simultaneous exposure to nCuO and PS-NPLs had a.n antagonistic effect on the growth inhibition of the microalgae, and nCuO played a leading role in the joint toxicity of nCuO and PS-NPLs. In comparison to nCuO exposure alone, combined exposure decreased the oxidative stress and alleviated the increase in the cell membrane permeability of microalgae. PS-NPLs could heteroaggregate with nCuO, which reduced the interaction between nCuO and microalgae, inducing decreased joint toxicity. Findings of this study will clarify our understanding of the joint toxicity of ENPs and NPLs.